2019
DOI: 10.3389/fonc.2019.00079
|View full text |Cite
|
Sign up to set email alerts
|

Time to Treatment Prediction in Chronic Lymphocytic Leukemia Based on New Transcriptional Patterns

Abstract: Chronic lymphocytic leukemia (CLL) is the most frequent lymphoproliferative syndrome in western countries. CLL evolution is frequently indolent, and treatment is mostly reserved for those patients with signs or symptoms of disease progression. In this work, we used RNA sequencing data from the International Cancer Genome Consortium CLL cohort to determine new gene expression patterns that correlate with clinical evolution.We determined that a 290-gene expression signature, in addition to immunoglobulin heavy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Chronic lymphocytic leukemia (CLL) is a disease with the accumulation of aberrant B cells in peripheral blood as well as proliferation and accumulation of CLL cells in the bone marrow and peripheral lymphoid organs. CLL patients are characterized by different prognoses, as well as profound molecular and immune defects [ 1 , 2 , 3 ]. Immune deregulations result in high susceptibility to infections as well as a failure to improve effective antitumor immune responses [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) is a disease with the accumulation of aberrant B cells in peripheral blood as well as proliferation and accumulation of CLL cells in the bone marrow and peripheral lymphoid organs. CLL patients are characterized by different prognoses, as well as profound molecular and immune defects [ 1 , 2 , 3 ]. Immune deregulations result in high susceptibility to infections as well as a failure to improve effective antitumor immune responses [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genes associated with time to treatment were used for a ML classifier from BigML (BigML, 2011) and showed high accuracy in predicting the need for treatment within the first 5 years following diagnosis. (Mosquera Orgueira et al, 2019). This application paves the way for the identification of high-risk patients using ML.…”
Section: Single Omic Studies In Cll and Applications Of Machine Learningmentioning
confidence: 94%
“…Mutations in the immunoglobulin heavy-chain variable region gene (IGHV) are correlated with better outcomes 6,7 , while mutations in NOTCH1, SF3B1, and BIRC3 are all correlated with poorer outcomes 8 . Transcriptomic profiling has been used to identify predisposition to the disease, severity, and time to treatment [9][10][11] . Relatively few studies have explicitly looked at longitudinal evolution of CLL; however, one recent genomic study showed that when sampled at multiple time points, many CLL patients have minimal genetic subclonal evolution during early disease development 12 .…”
Section: Introductionmentioning
confidence: 99%